Sustainable Public Transportation Service Quality Assessment by a Hybrid Bayesian BWM and Picture Fuzzy WASPAS Methodology: A Real Case in Izmir, Turkey - Tumsekcali, Ecem; Taskin, Alev (MDPI, 2025)
Especially in crowded cities, the public transportation system is one of the most crucial elements that influences quality of life and also demonstrates progress. For this purpose, a new SERVQUAL model, expanded with sustainability and Industry 4.0 dimensions, is proposed to evaluate service quality in the public transport system. This model, called SPT SERVQUAL 4.0 (Sustainable Public Transport SERVQUAL 4.0), is created with a three-level hierarchical criteria structure by developing the structure of the traditional SERVQUAL model. First of all, criteria weights are determined using the Bayesian Best-Worst Method (BWM) and expert evaluations for each level. Afterwards, the Picture Fuzzy WASPAS method is applied in order to rank the public transportation alternatives using the obtained criteria weights. The proposed hybrid methodology is applied on a real case study of five different bus alternatives in the Izmir public transportation system. As a result, the best public transportation bus alternative is found to be electric buses. The study, which adapts the dimensions of Industry 4.0 and sustainability, two of the most important issues of our age, to the evaluation of public transport system service quality, contributes by providing insights into system improvement and strategy development in the public or private sector.
Keywords: Bayesian BWM; WASPAS; picture fuzzy sets; public transport; sustainability; SERVQUAL; CUSTOMER SATISFACTION; TRANSIT; PERCEPTIONS; SYSTEMS; MODEL; MCDM; PERFORMANCE; FRAMEWORK; AHP; Science & Technology - Other Topics; Environmental Sciences & Ecology